2002
DOI: 10.1523/jneurosci.22-21-09513.2002
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Fingerprints for Major Histocompatibility Complex-Determined Body Odors II: Relationship among Odor Maps, Genetics, Odor Composition, and Behavior

Abstract: The olfactory system detects small differences in the composition of natural odorants, made up of hundreds of molecules. Odorous quality is hypothetically represented by a combinatorial code: activation of distinct but overlapping subsets of olfactory receptors resulting in activation of a distinct subset of glomeruli in the main olfactory bulb (MOB). Here we show that modification of a single gene (the K gene of the major histocompatibility locus), which results in a subtle change in the odiferous quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
105
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(114 citation statements)
references
References 38 publications
8
105
1
Order By: Relevance
“…The localization of the TRPM5-GFP-positive glomeruli in the ventral area of the olfactory bulb was intriguing because this area overlaps with domains responsive to mouse urine and putative pheromones (22,(32)(33)(34)) (see SI Movie 1). To determine whether the TRPM5-GFP-positive glomeruli respond to these semiochemicals, we surveyed odor responsiveness of glomeruli by detecting neuronal activity-dependent Fos protein expression in the periglomerular cells surrounding glomeruli.…”
Section: Gfp Expressionmentioning
confidence: 99%
“…The localization of the TRPM5-GFP-positive glomeruli in the ventral area of the olfactory bulb was intriguing because this area overlaps with domains responsive to mouse urine and putative pheromones (22,(32)(33)(34)) (see SI Movie 1). To determine whether the TRPM5-GFP-positive glomeruli respond to these semiochemicals, we surveyed odor responsiveness of glomeruli by detecting neuronal activity-dependent Fos protein expression in the periglomerular cells surrounding glomeruli.…”
Section: Gfp Expressionmentioning
confidence: 99%
“…Activity mapping studies have shown that glomeruli within this area of the olfactory bulb are most responsive to urinary odors (Schaefer, Yamazaki, Osada, Restrepo, & Beauchamp, 2002;Xu et al, 2005), and that c-Fos expression in associated periglomerular cells in this part of the olfactory bulb is increased by urine exposure. For each animal, four sections at approximately Bregma 1.70mm (see Figure 1a) were selected for the anterior piriform cortex and c-Fos neurons were bilaterally counted within a 600µm x 450µm box laid over this area.…”
Section: Exposure To Estrous Urine and C-fos Immunohistochemistrymentioning
confidence: 99%
“…Recently [6] a class of 'trace amineassociated receptors' was identified in the MOE which respond to volatile amines emitted from mouse urine. A series of studies by Restrepo and co-workers [13,12,7] showed that volatile urinary odors from male mice augmented Fos expression in juxtaglomerular cells of the MOB (an index of glomerular activation) of female conspecifics. More recently, Martel and Baum [9] used this same method to show that urinary volatiles from male versus estrous female mice activated overlapping, but distinguishable clusters of glomeruli located in the ventral portion of the MOB in both sexes.…”
mentioning
confidence: 99%
“…The location of each activated glomerulus was mapped according to radial angle from a central point of origin and rostral-caudal distance through the bulb. Activated glomeruli were defined as having 180 • of continuous Fos activation or two 90 • arcs of Fos activation in the periglomerular cells surrounding the glomerulus [13,12]. Olfactory bulbs were sectioned perpendicular to the lateral olfactory tract to insure proper orientation, and sections were analyzed in sequence (70 m between sections).…”
mentioning
confidence: 99%
See 1 more Smart Citation